2019
DOI: 10.1002/jaba.562
|View full text |Cite
|
Sign up to set email alerts
|

Noncontingent and differential reinforcement in the treatment of pediatric feeding problems

Abstract: We conducted functional analyses of the inappropriate mealtime behavior of 5 children diagnosed with feeding problems. Then, we compared the effects of differential and noncontingent reinforcement, and the relative effects of escape extinction with and without differential or noncontingent reinforcement, when escape extinction appeared necessary. Both reinforcement procedures were effective without escape extinction to treat food refusal for 1 child, but only differential reinforcement was effective without es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Tangible access procedures have been shown in the past to reduce inappropriate mealtime behaviour during extinction bursts (e.g., Berth et al, 2019;Piazza, Patel, Gulotta, Sevin, & Layer, 2003;Reed et al, 2004). Noncontingent access did not reduce negative vocalisations for Préjean in the treatment evaluation.…”
Section: Discussionmentioning
confidence: 69%
“…Tangible access procedures have been shown in the past to reduce inappropriate mealtime behaviour during extinction bursts (e.g., Berth et al, 2019;Piazza, Patel, Gulotta, Sevin, & Layer, 2003;Reed et al, 2004). Noncontingent access did not reduce negative vocalisations for Préjean in the treatment evaluation.…”
Section: Discussionmentioning
confidence: 69%
“…It is possible that the use of EE may have resulted in more efficient treatment effects relative to NCR alone without any of the previously described side effects (e.g., extinction bursts). For example, Berth et al (2019) showed that positive reinforcement (i.e., DRA and NCR) enhanced the effects of extinction. Third, we did not evaluate DRA without NCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have examined the effects of positive reinforcement (e.g., differential reinforcement [DRA] and noncontingent reinforcement [NCR]) both in conjunction with and in the absence of EE during the treatment of pediatric feeding disorders. Although findings have been mixed (Berth et al, 2019;Reed et al, 2004), results of a number of studies have shown that positive reinforcement may be effective in the treatment of pediatric feeding disorders in the absence of EE for some individuals. For example, Wilder et al (2005) evaluated NCR without EE as treatment for food refusal and escape-maintained self-injurious behavior (SIB) emitted by a 3-year-old female diagnosed with ASD.…”
mentioning
confidence: 99%
See 2 more Smart Citations